Dalit Christians in South India : caste, ideology and lived religion - Mocherla, Ashok Kumar (New York: Routledge, 2021)
Study on Dalit Lutherans belonging to Mala caste in Dravidapuram village, Andhra Pradesh.
Originally presented as the author's theses (Doctoral)--Indian Institue of Technology Bombay: under title: "Christians of Coastal Andhra: a sociological study".
Includes bibliographical references (pages 127-133) and index.
Keywords: Lutherans -- India -- Dravidapuram; Malas -- India -- Dravidapuram -- Religion; Malas -- India -- Dravidapuram -- Ethnology; Malas -- Political activity -- India -- Dravidapuram; Dalits -- India -- Dravidapuram -- Religion; Christianity -- India -- Andhra Pradesh; Dravidapuram (India) -- Religion